2010
DOI: 10.1155/2011/569068
|View full text |Cite
|
Sign up to set email alerts
|

Rodent Preclinical Models for Developing Novel Antiarthritic Molecules: Comparative Biology and Preferred Methods for Evaluating Efficacy

Abstract: Rodent models of immune-mediated arthritis (RMIA) are the conventional approach to evaluating mechanisms of inflammatory joint disease and the comparative efficacy of antiarthritic agents. Rat adjuvant-induced (AIA), collagen-induced (CIA), and streptococcal cell wall-induced (SCW) arthritides are preferred models of the joint pathology that occurs in human rheumatoid arthritis (RA). Lesions of AIA are most severe and consistent; structural and immunological changes of CIA best resemble RA. Lesion extent and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
121
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(126 citation statements)
references
References 148 publications
3
121
0
1
Order By: Relevance
“…Paws selected for histology are fixed in formalin, decalcified, and processed to sagittal hemisections representing larger (eg, tarsal, carpal) as well as smaller digital joints. 3 Some investigators prefer to embed the hind paws in the sagittal plane, whereas forepaws are oriented horizontally. In addition to the usual considerations for histology, particular attention should be given to sample preparation.…”
mentioning
confidence: 99%
“…Paws selected for histology are fixed in formalin, decalcified, and processed to sagittal hemisections representing larger (eg, tarsal, carpal) as well as smaller digital joints. 3 Some investigators prefer to embed the hind paws in the sagittal plane, whereas forepaws are oriented horizontally. In addition to the usual considerations for histology, particular attention should be given to sample preparation.…”
mentioning
confidence: 99%
“…16 These models have proven to predict the responsiveness of human RA patients. Structural and immunological changes in CIA best resemble RA, while AIA lesions are most severe and consistent.…”
Section: Discussionmentioning
confidence: 99%
“…The widespread formation of osteophytes along the periosteal surface may eventually result in fusion (ankylosis) of the affected joints with joint deformities resulting in a significant reduction of mobility. 16 Hence, the study duration was restricted to 3 weeks to include the acute and chronic phases of rat CIA. Symptomatic rats received analgesic treatment.…”
Section: Animal Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…1, with these exceptions: CCL2, chemokine (C-C motif) ligand 2 (formerly MCP-1); chemokine (C-X-C motif) ligand 1 (formerly KC/GRO); RANKL, receptor activator of nuclear factor-B. Gross images reprinted from (Bolon et al 2011), while the cytokine signatures were reported in (Stolina et al 2008(Stolina et al , 2009 patients with comparable conditions. Human patients with RA have similar clinical and pathological presentations, but the AIDx is nonetheless a heterogeneous condition in which some patients respond only to interleukin (IL)-1 inhibition, others improve with tumor necrosis factor-a (TNF-a) blockade, still others recover following anti-IL-6 therapy, and some are not helped by quenching any of these ''master'' cytokines (Fitzgerald et al 2005;Senolt et al 2009;Patel and Moreland 2010;Turkstra, Ng, and Schuffham 2011).…”
mentioning
confidence: 99%